2008
DOI: 10.1007/s12011-008-8155-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Iodine Uptake by Cabbage: Effects of Iodine Species and Where It is Stored

Abstract: Iodine-enhanced vegetable has been proven to be an effective way to reduce iodine deficiency disorders in many regions. However, the knowledge about what mechanisms control plant uptake of iodine and where iodine is stored in plants is still very limited. A series of controlled experiments, including solution culture, pot planting, and field experiments were carried out to investigate the uptake mechanism of iodine in different forms. A new methodology for observing the iodine distribution within the plant tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 13 publications
4
40
0
1
Order By: Relevance
“…In soil solutions, the major chemical species of soluble iodine are generally thought to be I − under flooded conditions (Muramatsu et al, 1989; Yuita, 1992) and IO − 3 under non-flooded conditions (Yuita, 1992). At similar concentrations, I − appears to be more phytotoxic than IO − 3 (Umaly and Poel, 1971; Mackowiak and Grossl, 1999; Zhu et al, 2003; Weng et al, 2008a). Böszörményi and Cseh (1960) suggested that IO − 3 is reduced to I − electrochemically before uptake by wheat roots.…”
Section: Discussionmentioning
confidence: 99%
“…In soil solutions, the major chemical species of soluble iodine are generally thought to be I − under flooded conditions (Muramatsu et al, 1989; Yuita, 1992) and IO − 3 under non-flooded conditions (Yuita, 1992). At similar concentrations, I − appears to be more phytotoxic than IO − 3 (Umaly and Poel, 1971; Mackowiak and Grossl, 1999; Zhu et al, 2003; Weng et al, 2008a). Böszörményi and Cseh (1960) suggested that IO − 3 is reduced to I − electrochemically before uptake by wheat roots.…”
Section: Discussionmentioning
confidence: 99%
“…However, throughout the years it has been shown that this technique alone is insufficient to ensure the total requirement of iodine (de Benoist et al, 2008), partly because the iodine of table salt is unstable and is subject to many losses by volatilization (Mottiar and Altosaar, 2011). In this regard, the consumption of iodine in organic forms such as seaweed and biofortified foods and yeast, is considered more appropriate (Funahashi et al, 2001; Weng et al, 2008a; Kopeć et al, 2015) because those organic sources are more stable than inorganic ones.…”
Section: Iodine and Human Healthmentioning
confidence: 99%
“…Plants can absorb iodine from the soil and it is assumed that in root cells iodine fluxes across membranes through putative H + /halide transporters and anion channels7. However, the molecular identities of such transporters have not yet been established78. Once inside the plant, a xylematic flux of iodine seems to be predominant46910, although a phloematic route for this element has been recently observed in tomato11.…”
mentioning
confidence: 99%